Catalytic asymmetric oxo-Diels–Alder reactions with chiral atropisomeric biphenyl diols - Yeung, Chi-Tung; Chan, Wesley Ting Kwok; Lo, Wai-Sum; Law, Ga-Lai; Wong, Wing-Tak (Beilstein Journal of Organic Chemistry, 2019)
New chiral atropisomeric biphenyl diols 3, 4 and 6 containing additional peripheral chiral centers with different steric bulkiness and/or electronic properties were synthesized. The X-ray crystal structure of 3 shows the formation of a supramolecular structure whereas that of 6, containing additional CF3 substituents, shows the formation of a monomeric structure. Diols 1–6 were found to be active organocatalysts in oxo-Diels–Alder reactions in which 2 recorded a 72% ee with trimethylacetaldehyde as a substrate.
Keywords: asymmetric organocatalysis; axial chirality; biaryls; hydrogen bond; oxo-Diels–Alder reaction